Incidence of Pediatric Community Associated Clostridium Difficile Infection Following Common Antibotics. (4th October 2017) - Katz, Margot Miranda; Parmar, Deepika; Dang, Rebecca; Alabaster, Amy; Greenhow, Tara
Abstract: Background: As rates of pediatric community-associated (CA) Clostridium difficile infection (CDI) increase, additional research is needed to address rates of infection following common antibiotics. Methods: This study was a retrospective review of the electronic health records of all children with stool specimens sent for C difficile from January first 2012 – December 31 st 2016 at Kaiser Permanente Northern California. Children with clinical symptoms consistent with CDI, confirmatory laboratory testing, no other identified causes of diarrhea, and community associated disease were defined as cases. Using outpatient and ED antibiotic prescription records for children, incidence rates were calculated for subsequent CA CDI for the most commonly prescribed antibiotics. Results: Of 507 primary CDI cases in our cohort, 327 had any antibiotic use 2012–2015. There were 205 primary CDI cases that were preceded by an antibiotic in the previous 1–365 days. Many of these patients had more than 1 antibiotic in the preceding year. Of those, rates of CA CDI were uncommon following common antibiotics. (Table) The highest rate of CA CDI followed ceftriaxone, cefdinir, ciprofloxacin and augmentin. The lowest rates were seen following penicillin, doxycycline and azithromycin. Ninety-three percent of the antibiotic prescriptions were in outpatients, 7% in inpatients. Conclusion: As rates of CA CDI increase, clinicians should be aware of rates of infection following administration of common antibiotics. The most common antibiotics to cause CA CDI were third-generation cephalosporins (ceftriaxone and cefdinir) and ciprofloxacin. Disclosures: All authors: No reported disclosures.